Combined Trans-Epithelial PRK and PTK for Treatment of Corneal Opacity Following Acanthamoeba Keratitis: A Case Report - Buonamassa R; Addabbo G; Pignatelli F; Niro A; Passidomo F (International Medical Case Reports Journal)
Rosa Buonamassa,1 Giuseppe Addabbo,2 Francesco Pignatelli,2 Alfredo Niro,2 Fedele Passidomo2 1Eye Clinic, P.O. “Madonna delle Grazie”, Matera, Italy; 2Eye Clinic, “SS. Annunziata” Hospital, ASL Taranto, Taranto, ItalyCorrespondence: Fedele Passidomo, Eye Clinic, “SS. Annunziata” Hospital, ASL Taranto, Via Francesco Bruno, 1, Taranto, 74121, Italy, Tel +393288569125, Email dotpaoli@yahoo.itPurpose: To report a case of Corneal Opacity following Acanthamoeba Keratitis (AK) treated successfully with transepithelial customized Photorefractive Keratectomy (PRK) combined with Photorefractive Keratectomy (PRK).Methods: One case report.Results: A 27-year-old woman was referred to our clinic for Acanthamoeba keratitis in her left eye. After 1 year from the infection, the patient returned to our attention for developing a central corneal scar and decreased corrected distance visual acuity (CDVA) in the left eye. The slit-lamp examination showed a central corneal opacity involving anterior stroma. A single-step topography-guided trans-epithelial PRK combined with PTK (CIPTA® 2 software, iVis Technologies) was performed in the left eye. After surface ablation using PRK, PTK was performed using masking agents (1% hydroxymethylcellulose) to smooth the ablated surface. Subsequently, 0.02% Mitomycin C was applied over the ablated surface. At the 1-month follow-up, a resolution of the corneal opacities was observed, with a visual improvement to 20/20, which was maintained at the 3-, 6-, and 12-months follow-up. Furthermore, there was an improvement in spherical equivalent and corneal morphological irregularity index.Conclusion: Corneal opacity following AK may be successfully treated using a combined topography-guided trans-epithelial PRK and PTK in selected patients.Keywords: Acanthamoeba keratitis, corneal degenerations, phototherapeutic keratectomy, topography-guided photorefractive keratectomy